Persisting Latino students at Colorado State University: their mentoring experiences - Salas, Rich A., author; Banning, Jim, advisor; Aragon, Antonette, advisor; Valdez, Norberto, committee member; Quick, Don, committee member (Colorado State University. Libraries, 2011)
This study examined the experiences of 17 Latino students who participated in the El Centro Resource Leaders Mentoring Program (ERLMP). The El Centro Resource Leaders Mentoring program at Colorado State University focuses on assisting incoming Latino/a freshman and transfer students with the transition to college by providing academic and cultural resources, involvement and leadership opportunities, and mentoring support. The purpose of the program is to assist Latino students to be successful and eventually graduate from Colorado State University. The program has been in place since 1994. All the participants in this study were currently serving or had served as Resource Leader Mentors within the last five years. The goal of the research was to understand the lived experiences of the students and their own perceptions of the reasons for their academic success and persistence. This study used an interpretive phenomenological analysis (IPA) of qualitative inquiry. Personal one-on-one interviews were conducted revealing thematic connections and interrelatedness of thoughts, patterns, and experiences that helped identify the essence of participants' experiences. The IPA approach allowed the researcher to explore the underlying meanings and experiences of undergraduate Latino students. The majority of the participants were first generation college students attending Colorado State University. Four major themes emerged from the data: Participants' Common Challenges, Participants' Common Experiences, Participant Benefits of Program, and Participants' Lessons Learned. The experiences of Colorado State University Latino students who had participated in the ERLMP provided valuable insights in understanding their mentoring experiences and what contributed to their persistence.
Keywords: Latino; students; persistence; mentoring